THE DETERMINANTS OF STOCK RETURNS FOR NON-BANKING COMPANIES LISTED ON THE LQ-45 INDEX AND THE SRI-KEHATI INDEX ON THE INDONESIAN STOCK EXCHANGE 2019–2023 - Santoso, Herry (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Investors rely on specific indicators to evaluate companies whose shares they intend to buy. These indicators typically include financial ratio analyses such as Profitability Ratios, specifically, Return on Assets (ROA) and Return on Equity (ROE). In addition to profitability, this study also considers the Liquidity Ratio, represented by the Current Ratio (CR), and the Solvency Ratio, represented by the Debt-to-Equity Ratio (DER), to assess a company's financial health. The research employs panel data regression analysis, combining time series and cross-sectional data, with stock returns as the dependent variable and the aforementioned financial ratios as independent variables. The selected independent variables, ROA, ROE, CR, and DER, are used to determine their influence on stock returns. The analysis shows that ROA, ROE, and DER have p-values greater than the 5% significance level, indicating they do not significantly affect stock returns. In contrast, CR has a p-value of 0.0008, which is below the 5% threshold, suggesting a statistically significant impact on stock returns.